Analisis Pengaruh Struktur Aktiva, Asset Turnover, Growth Terhadap Profitability Melalui Variabel Capital Structure Sebagai Variabel Intervening (Studi Kasus pada Perusahaan Consumer Goods BEI Periode Tahun 2012-2014) - Wardhana, Iga Bagus Jaya; Mawardi, Wisnu (Diponegoro Journal of Management, 2016)
The objectives of this research are to find and analyze connection between Assets Structure, asset turnover, growth asset, to profitability. In this case, Capital Structure become a intervening variable to know the relationship between  Asset Structure, total asset turnover, growth asset to profitability.            This research conducted in manufacture companies on consumer goods sector that listed in Indonesian Stock Exchanges on period 2012-2014. The data used in this research is from financial report on Indonesian Stock Exchanges. The method of this research is using quantitative approach with path analysis. The sample used is 26 companies with specific criteria.            The result show that Asset Structure have a positive significant impact to the capital structure. Total asset turnover have a negative impact to capital structure. Growth asset don’t have any impact to capital structure. Assets Structure have a positive significant impact to profitability. Total asset turnover have a positive significant impact to the profitability and growth asset don’t have any impact to profitability.